AYURVEDIC MANAGEMENT OF TWAK GRANTHI-A CASE STUDY - K.Vasudeva Reddy (International Journal of Applied Ayurved Research, 2018)
56 years old male presented with history of irregular growth on plantar aspect of the right foot just below the second toe with pain since 3 years. This case diagnosed as Twak granthi by physical examination, history of recurrence after multiple operations .This case is treated with ayurvedic medicines Lohasasavam, Saribadyasavam, Sameerapannaga ras, and Aswagandha choornam successfully.